Syntactic Errors and Binding-Related Referential Issues in ESL Academic Writing - ROBLES, FLORENCE (International Journal of Language and Literary Studies, 2026)
This study investigated the syntactic errors and Binding Principle-related issues in the academic writing of Bachelor of Physical Education (BPED) pre-service teachers in a Philippine ESL context. Guided by Error Analysis and Binding Theory, the study analyzed student essays to identify patterns of grammatical and referential difficulties. The findings revealed that the most frequent syntactic errors involved word forms (28.18%), articles (19.09%), and subject-verb agreement (12.73%), indicating persistent challenges in functional grammar. In terms of binding-related issues, only one violation of Principle A (9.09%) was identified, while no violations of Principles B and C were observed. However, pronoun agreement and reference errors accounted for the majority of referential issues (72.73%), followed by reflexive formation errors (18.18%). These findings suggest that learners’ difficulties are primarily associated with discourse-level referential clarity rather than violations of core syntactic principles. Pedagogically, the results highlight the need for ESL instruction to integrate grammar and discourse-level competencies, particularly in teaching pronoun use and cohesion. For teacher education, especially in BPED programs, the findings underscore the importance of strengthening pre-service teachers’ academic writing competence. The study contributes to a context-specific understanding of ESL writing challenges in Philippine tertiary education.